2015
DOI: 10.4236/abcr.2015.42005
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Survival in Cameroon: Analysis of a Cohort of 404 Patients at the Yaoundé General Hospital

Abstract: This study aimed to estimate the survival rate of breast cancer in a group of patients followed up at the Yaoundé General Hospital in Cameroon. A retrospective review of records of patients managed for breast cancer between 1995 and 2007 was carried out at the Yaoundé General Hospital. Survival analysis was carried out with survival defined as the time between the date of unequivocal diagnosis of cancer and the date of last follow-up or death. Survival curves were plotted in R.3.1.1 software. Mean age of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 16 publications
5
21
2
Order By: Relevance
“…Previous data showed that the 5-year mortality was from 36% to 38% in Sub-Saharan Africa [22]- [24]. The overall survival and disease-free survival 57.9% and 64.3% respectively are similar to other previous studies performed in the developing countries [25]- [29] ( Table 4).…”
Section: Discussionsupporting
confidence: 86%
“…Previous data showed that the 5-year mortality was from 36% to 38% in Sub-Saharan Africa [22]- [24]. The overall survival and disease-free survival 57.9% and 64.3% respectively are similar to other previous studies performed in the developing countries [25]- [29] ( Table 4).…”
Section: Discussionsupporting
confidence: 86%
“…In our study, the overall median survival for histologically confirmed breast cancer was 56.5(95% CI, 53.46 -60.83) months. Our results were higher than the previous studies in which the median survival was 24 months in Cameroon (25),40 months in Sudan (30) ,but lower than to the result reported from Malaysia the median survival was 68.1 months (23). Although, our study showed higher overall median survival than that seen in the Cameroon and Sudan studies, the lower value obtained in comparison with Malaysia is most probably due to shorter period of study in ours.…”
Section: Discussioncontrasting
confidence: 91%
“…This finding is in contrary with studies done in different Africa and Asian countries (25,27,33).Which identified breast-conserving surgery, have better survival than mastectomy.…”
Section: Discussioncontrasting
confidence: 91%
“…In Cameroon appropriately, the median survival rate after five years is still weak (around 40%) as compared with developed countries. In addition, 57.9% of breast cancer patients are under 50 years, and 28.5% are less than 40 years [ 17 ]. Due to the high frequency with which breast cancer reaches the human population, the quest for effective and less expensive medical treatment becomes a serious need.…”
Section: Discussionmentioning
confidence: 99%